Antispasmodic effect of asperidine b, a pyrrolidine derivative, through inhibition of l-type ca2+ channel in rat ileal smooth muscle - Acharaporn Duangjai (2022)
Antispasmodic agents are used for modulating gastrointestinal motility. Several compounds isolated from terrestrial plants have antispasmodic properties. This study aimed to explore the inhibitory effect of the pyrrolidine derivative, asperidine B, isolated from the soil-derived fungus Aspergillus sclerotiorum PSU-RSPG178, on spasmodic activity. Isolated rat ileum was set up in an organ bath. The contractile responses of asperidine B (0.3 to 30 µM) on potassium chloride and acetylcholine-induced contractions were recorded. To investigate its antispasmodic mechanism, CaCl2, acetylcholine, Nω-nitro-L-arginine methyl ester (L-NAME), nifedipine, methylene blue and tetraethylammonium chloride (TEA) were tested in the absence or in the presence of asperidine B. Cumulative concentrations of asperidine B reduced the ileal contraction by ~37%. The calcium chloride and acetylcholine-induced ileal contraction was suppressed by asperidine B. The effects of asperidine B combined with nifedipine, atropine or TEA were similar to those treated with nifedipine, atropine or TEA, respectively. In contrast, in the presence of L-NAME and methylene blue, the antispasmodic effect of asperidine B was unaltered. These results suggest that the antispasmodic property of asperidine B is probably due to the blockage of the L-type Ca2+ channel and is associated with K+ channels and muscarinic receptor, possibly by affecting non-selective cation channels and/or releasing intracellular calcium.